Pengaruh Pendidikan Kesehatan terhadap Tingkat Pengetahuan tentang Cuci Tangan Pakai Sabun Pada Siswa MIS Karya Thaiyyibah Kayumalue Pajeko - Katrina Feby Lestari; Dewi Kuntuamas; Sringati Sringati (Universitas Muhammadiyah Manado, 2019)
The problem found in MIS Karya Thaiyyibah of Kayumalue Pajeko mentioned that there are 4 students do not understand what meaning and steps of hand washing and 2 students do not understand why hand washing with soap is important. This research aims to obtain the influences of health education toward knowledge level regarding hand washing with soap of MIS Karya Thaiyyibah students, Kayumalue Pajeko. This is quantitative research with pre-experimental design by one grup pretest-postest design. Sampling number is 24 students that taken by total sampling technique. Result of univariate shown that before doing the health education, about 12 students (50%) have enough knowledge and after it about is students (75%) have good knowledge regarding it. Bivariate analyses by Wilcoxon test and found that there is influences of health education toward knowledge level about hand washing with soap of MIS Karya Thaiyyibah Student of Kayumalue Pajeko with p value = 0,003. Conclusion that there is influences of health education toward knowledge level obout hand washing with soap of MIS Karya Thaiyyibah students of Kayumalue Pajeko. Expeeted that sehoul administration could collaborate with health worker in providing the health education regarding hand washing with soap properly to improve student’s knowledge.